Analytical and numerical modelling of shear-link device for seismic energy dissipation in frame structures. (1st July 2020) - Nuzzo, Iolanda; Losanno, Daniele; Cilento, Fabrizia; Caterino, Nicola
Highlights: Preliminary sizing tool for steel shear link damper SL, experimentally calibrated. Development of simplified analytical models for SL mechanical behavior prediction. Development of refined numerical model for SL nonlinear response prediction. Comparative assessment of analytical, experimental and numerical models results. Abstract: With the continuous development of new supplemental seismic control systems, recent research advancements can be applied to structures located in earthquake-prone zones. Several energy dissipation devices have been conceived and experimentally investigated. However, until a comprehensive design procedure that incorporates all parameters of the control system is formulated, the applications of these devices remain limited. The present study is part of a research project about a particular shear-link (SL) dissipative device. It has been recently introduced for an effective seismic protection of structures, also installed for many real applications, especially in South America. Starting from experimental data, an ABAQUS finite-element nonlinear model of such device is presented. It is suitably tuned to simulate the combined isotropic/kinematic hardening response of the SL device. It also provides a deeper understanding of the overall nonlinear behavior of the device, so as to laid the foundations for a simplified modelling approach the authors propose in the second part of the work. The latter is an approximate analytical model able to predict initial stiffness of the SL device, yielding force, as well as the equivalent damping ratio at large displacement. Alternative models for stiffness are also introduced and compared for complexity and accuracy. The final aim is that of providing a reliable yet simple tool the professionals can use to include SL devices in a fully integrated and manageable design process. The assessment of the accuracy of both analytical and numerical models is based on the available experimental data. The results as well as the involved approximation are presented and discussed.